PENYIDIKAN TERHADAP TINDAK PIDANA PENYELUNDUPAN MINUMAN KERAS YANG MENGANDUNG ETIL ALKOHOL DI WILAYAH HUKUM DIREKTORAT JENDERAL BEA DAN CUKAI TIPE MADYA PABEAN B KOTA PEKANBARU - Fajar, Muhammad Abdul; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Smuggling crime is a serious problem in the implementation of thecountry's economy. one item that is often smuggled into the country of Indonesiais liquor. Liquids are excise-related goods containing ethyl alcohol where thegoods are specific and characteristic while negative impacts are necessary so thatthe circulation of beverages containing ethyl alcohol is necessary. Office of theDirectorate General of Customs and Excise Type Medium Customs B, PekanbaruCity, one of the efforts to eradicate smuggling.This type of research can be classified in the type of sociological legalresearch (empirical), because in this study the authors immediately conductresearch on the location or place under study in order to provide a complete andclear picture of the problem under study. This research was conducted in the legalarea of the Directorate General of Customs and Excise of Pekanbaru City, whilethe population and samples were. Head of Counseling and Information Servicessection of the Supervision Office, Customs and Excise Service of Pekanbaru CityB and Manufacturer of ape drinks. The data sources used are primary data, andsecondary data. Data collection techniques in this study were interviews,questionnaires, and literature review.The conclusion that can be obtained from the results of the study is theInvestigation of Alcoholic Smuggling Crimes Containing Ethyl Alcohol is carriedout if the perpetrator of the smuggling is caught and fulfilled the element ofcriminal acts in the field of customs. with repressive law enforcement(prosecution). Obstacles in the investigation of criminal acts of liquor smugglingcontaining ethyl alcohol in the jurisdiction of the Directorate General of Customsand Excise of the Type of Customs, B Customs of the City of Pekanbaru, there are2 (two) factors, namely internal factors and external factors. Interanl factorsconsist of lack of personnel and lack of operational facilities. while externalfactors consist of smuggling offenders who do not directly engage in smuggling,the number of unofficial ports, shipping lines and the lack of observations throughthe Inteijen Team to found immediately a liquor dealer or smuggler containingEthyl Alcohol.Keywords: Investigation, Crime, Smuggling, Liquor, Containing Ethyl Alcohol